Changes in causal attributions and relationship representations: are they specific or common mechanisms in the treatment of depression? - Zilcha-Mano, Sigal; Chui, Harold; Dolev, Tohar; McCarthy, Kevin S.; Dinger, Ulrike; Barber, Jacques P. (Journal of affective disorders, 2016)
Background - The goal of the study was to examine two central theory-driven mechanisms of change, causal attributions and relational representations, to account for symptomatic improvement in psychodynamic treatment and supportive clinical management, combined with either pharmacotherapy or placebo, in a randomized control trial (RCT) for depression. - Method - We used data from an RCT for depression, which reported non-significant differences in outcome among patients (N=149) who received supportive-expressive psychotherapy (SET), clinical management combined with pharmacotherapy (CM+MED), or clinical management with placebo pill (CM+PBO) (Barber et al., 2012). Mechanism and outcome measures were administered at intake, mid-treatment, end of treatment, and at a 4-month follow-up. - Results - Improvements in causal attributions and in relational representations were found across treatments. Changes in causal attributions did not predict subsequent symptomatic level when controlling for prior symptomatic level. In contrast, decrease in negative relational representations predicted subsequent symptom reduction across all treatments, and increase in positive relational representations predicted subsequent symptom reduction only in SET. - Limitations - The study is limited by its moderate sample size. Additional studies are needed to examine the same questions using additional treatment orientations, such as cognitive treatments. - Conclusions - Findings demonstrate that changes in negative relational representations may act as a common mechanism of change and precede symptom reduction across psychodynamic therapy and supportive case management combined with either pharmacotherapy or placebo, whereas an increase in positive relational representation may be a mechanism of change specific to psychodynamic therapy.
Gesehen am 22.09.2020
Available online 31 December 2015